2023
DOI: 10.46234/ccdcw2023.134
|View full text |Cite
|
Sign up to set email alerts
|

An Autoregressive Integrated Moving Average Model for Predicting Varicella Outbreaks — China, 2019

Abstract: Introduction: Varicella, a prevalent respiratory infection among children, has become an escalating public health issue in China. The potential to considerably mitigate and control these outbreaks lies in surveillance-based early warning systems. This research employed an autoregressive integrated moving average (ARIMA) model with the objective of predicting future varicella outbreaks in the country.Methods: An ARIMA model was developed and fine-tuned using historical data on the monthly instances of varicella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…In previous studies, the ARIMA model was commonly used to study the trend of infectious diseases and chronic non-infectious disease, such as the varicella [54], pulmonary tuberculosis [55], malaria [56], pertussis [57], Corona Virus Disease 2019 (COVID-19) [58], chronic kidney disease [59], diabetes [60], cardiovascular diseases [61] and economic burden of these diseases. In this study, the Ljung-Box test and sensitivity analysis demonstrated that the model exhibited a good fit and accurately predicted outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the ARIMA model was commonly used to study the trend of infectious diseases and chronic non-infectious disease, such as the varicella [54], pulmonary tuberculosis [55], malaria [56], pertussis [57], Corona Virus Disease 2019 (COVID-19) [58], chronic kidney disease [59], diabetes [60], cardiovascular diseases [61] and economic burden of these diseases. In this study, the Ljung-Box test and sensitivity analysis demonstrated that the model exhibited a good fit and accurately predicted outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…DBN estimation employs various machine learning algorithms, notably the LASSO algorithm in this research, along with James-Stein shrinkage estimation and first-order conditional dependence approximation ( 30 , 36 , 37 ). Despite this, the SARIMA method is also recognized for its robust fitting and predictive capabilities ( 34 , 38 , 39 ). Given our data’s specific characteristics, we found SARIMA to surpass both the DBN and ARIMA methods in performance.…”
Section: Discussionmentioning
confidence: 99%